Optimization of the Geometrical Parameters for the Output Mirror in a He-Ne Laser - Abdul-Rahim, Delshad O.; Mawlud, Saman Q. (Science Journal of University of Zakho, 2013)
The aim of this study is to produce a model via iterative description of the beam distribution to connect the output power of a He-Ne, continuous and low power laser in terms of its beam radius by operating it as regular pattern of repeated wave front with in the space between the mirrors. Because of the spherical shapes of laser resonators have complete Gaussian shapes. Hence the beam radius changes according to its position and along the principle axis of the cavity. We used a LASCAD simulation program as an analyzer for our data; the results didn’t change that much with those of original Gaussian beam model.
Keywords: He-Ne laser; Gaussian beam, Iteration; beam quality